Elicitation of immune responses against Nipah virus by an engineered synthetic DNA vaccine - Choi, Hyeree; Kudchodkar, Sagar B.; Xu, Ziyang; Ho, Michelle; Xiao, Peng; Ramos, Stephanie; Humeau, Laurent; Weiner, David B.; Muthumani, Kar (Frontiers in Virology, 2022)
Nipah virus (NiV) is a re-emerging pathogen that causes severe disease in animals and humans. Current treatment measures for NiV infection are insufficient, and there is no approved vaccine against NiV for either humans or animals. Nipah virus is listed as a high-priority pathogen for vaccine and therapeutic research by the World Health Organization (WHO). In the present study, we employed synthetic enhanced DNA technologies developed to design and produce novel consensus NiV Fusion (NiV-F) and Glycoprotein (NiV-G) antigen sequences for inclusion in synthetic DNA vaccines for NiV. The expression of each vaccine antigen was confirmed in vitro using immune-binding assays. Electroporation-enhanced intramuscular injection of each NiV-F and NiV-G into mice induced potent cellular immune responses to multiple epitopes of NiV-G and NiV-F that included antigen-specific CD8+ T cells. Both vaccines elicited high antibody titers in mice, with a single immunization sufficient to seroconvert 100% of immunized animals. Additionally, the NiV-F vaccine also induced antibodies to neutralize NiV-F-pseudotyped virus particles. These data support further study of these novel synthetic enhanced NiV nucleic acid-based antigens as potential components of an effective vaccine against the Nipah virus.